Andrew Stewart correspondence - Stewart, Andrew, 1791-1872.
ALS (Washington, D.C.) written by Stewart to Gabriel Hiester relating to national and Pennsylvania politics in anticipation of Andrew Jackson's presidential administration.
U.S. representative from Pennsylvania.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hiester, Gabriel, -- 1779-1831 -- Correspondence; Jackson, Andrew, -- 1767-1845.; Pennsylvania -- Politics and government -- 1775-1865.; United States -- Politics and government -- 1829-1837.; Representatives, U.S. Congress -- Pennsylvania